Studi ketoksikan dinoflagelata spesies Prorocentrum minimum (Dinophyceae) Schiller (Pavillard) - ., Rozirwan; Usup, Gires (Maspari Journal : Marine Science Research, 2010)
This study was carried out to determine the toxicity of the dinoflagellate Prorocentrum minimum species that formed massive blooms in Lido Beach, Johor Bahru in July 2002. Clone cultures were established in ES-DK medium at 26o C under a 14:10 hour light dark cycle. Species toxicity was determined by intra peritoneal (i.p) injection of culture extract into mice. Cultured cell extracts were toxic to mice. The major symptoms were muscular paralysis and diarrhea. However no mouse mortality was observed even after 13 hours.Ã‚Â  Extracts of cultured cells were also hemolytic on rabbit red blood cells. Keywords: Dinoflagellate, HAB, Prorocentrum minimum, Red Tide dan Toxicity Kajian dilakukan untuk menentukan ketoksikan dinoflagelata spesies Prorocentrum minimum yang menyebabkan kejadian pasang merah besar-besaran di perairan Pantai Lido, Johor Bahru pada Juli tahun 2002. Kultur klon telah dibuat dalam medium ES-DK pada suhu 26o C dan siklus pencahayaan 14:10 jam terang gelap. Ketoksikan spesies diuji dengan penyuntikan ekstrak kultur secara intra peritoneal (i.p.) terhadap tikus. Hasil pengamatan menunjukan ekstrak sel yang dikultur memberikan pengaruh racun kepada tikus. Gejala utama adalah kejang otot dan menceret/diare. Walau bagaimanapun tidak didapati tikus yang mati setelah dilakukan pengamatan selama 13 jam. Ekstrak toksin spesies ini juga menunjukkan pengaruh hemolitik terhadap eritrosit kelinci. Kata kunci: Dinoflagellata, HAB, Prorocentrum minimum, Red Tide dan Toxicity